In memoriam Prof. Dr. dr. Saptawati Bardosono, MSc - Pittara Pansawira; Luciana Budiati Sutanto (World Nutrition Journal, 2022)
The passing of Prof. Saptawati Bardosono on October 15th last year was a great sadness and loss for the entire scientific community, especially nutrition-related. It was also an immeasurable grief for us, the editorial team of World Nutrition Journal.